Integrated battery charging circuit and model predictive current controller for hybrid electric vehicles - Kang, Ho Sung; Kim, Seok Min; Lee, Kyo Beum (Conference Proceedings - IEEE Applied Power Electronics Conference and Exposition - APEC, 2019)
This paper proposes a circuit design of single-phase bi-directional on-board charger (OBC) using starter generator and its drive inverter in hybrid electric vehicles (HEVs). There are numerous power electronics components in a HEV. The proposed circuit has a battery charging ability by adding power relays into the generator drive system. Therefore, the conventional OBC can be removed from the vehicle and thus the power density of the vehicle is increased. Because the proposed charging circuit allows bi-directional power delivery from grid to vehicle, a model predictive current controller is proposed to achieve the fast-dynamic response and improve the harmonic characteristic of grid current. The simulation results verify the validity and feasibility of the proposed integrated charging system design and its control method.
Keywords: Current controller; Fast dynamic response; Grid connected systems; Harmonic characteristics; Hybrid electric vehicles (HEVs); On-board charger; Power flows; Starter generators; Bi-directional power flow; Grid-connected system; Hybrid electric vehicles; Model predictive control; On-board charger